2018
DOI: 10.1038/s41598-018-35271-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent metabolic changes in HIV-infected patients during the first year of combination antiretroviral therapy

Abstract: The HIV-human metabolic relationship is a complex interaction convoluted even more by antiretroviral therapy (cART) and comorbidities. The ability of cART to undo the HIV induced metabolic dysregulation is unclear and under-investigated. Using targeted metabolomics and multiplex immune biomarker analysis, we characterized plasma samples obtained from 18 untreated HIV-1-infected adult patients and compared these to a non-HIV infected (n = 23) control population. The biogenic amine perturbations during an untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 57 publications
(57 reference statements)
9
52
0
Order By: Relevance
“…Dillon et al and Brenchley et al stated that the altered microbiome is associated with systemic inflammation; these findings may be the reason for altered metabolism [38,39]. Peltenburg et al have found impaired biogenic amine levels in an untreated HIV(+) patient group [40]. Metabolic dysregulation was also common in this study; biogenic amine disturbances may have a role in the metabolic effects of HIV as well.…”
Section: Discussionsupporting
confidence: 56%
“…Dillon et al and Brenchley et al stated that the altered microbiome is associated with systemic inflammation; these findings may be the reason for altered metabolism [38,39]. Peltenburg et al have found impaired biogenic amine levels in an untreated HIV(+) patient group [40]. Metabolic dysregulation was also common in this study; biogenic amine disturbances may have a role in the metabolic effects of HIV as well.…”
Section: Discussionsupporting
confidence: 56%
“…The use of ART to control HIV-1 has been associated with a number of cellular changes [44][45][46][47]. Since EpKS patients in our cohort had varying ART duration and some with detectable plasma HIV-1 viral load despite ART treatment, we tested the effect of ART duration and HIV-1 viremia on EpKS transcriptome profiles.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Whether the same dysregulations, or similar magnitude of changes, occur in EnKS, has not been investigated. Because lipid metabolic dysregulation is common in ART treated HIV-1 infected individuals [44][45][46][47], it will be important to determine whether the KS-associated lipid metabolism defects are due to KSHV infection, attributable to HIV-1 co-infection or result from ART. Moreover, a male gender bias in KS has been noted, especially for classical and EnKS, suggesting a potential involvement of androgens or androgen receptors in the disease pathogenesis [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“… The Bio-Plex® 200 system Luminex analyser, Bio-Rad, CA, USA Plasma inflammation and cell stress biomarkers : In a subgroup of MIPs with different durations of exposures to ART from pregnancy to 12 months of age At least 25 inflammatory chemokines and cytokines measurements. The Bio-Plex® 200 system Luminex analyser, Bio-Rad, CA USA Plasma metabolomics: > 400 analytes, in a subgroup of MIPs with different durations of exposures to ART from pregnancy to 12 months of age to assess altered amino acid and lipid metabolism 3 platforms -Biogenic amines (Amino acids, catecholamines & polyamines), Signalling lipids (Sphingosine-1-phosphate etc., Positive lipids (Lysophospholipids, phospholipids, cholesterol esters, di/triglycerides & sphingomyelins) as described [ 76 ]. UPLC; TQMS; QToF –HPLC; UHPLC –; MS/MS – Triple Quadrupole Mass Spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…-Biogenic amines (Amino acids, catecholamines & polyamines), Signalling lipids (Sphingosine-1-phosphate etc., Positive lipids (Lysophospholipids, phospholipids, cholesterol esters, di/triglycerides & sphingomyelins) as described [ 76 ].…”
Section: Methodsmentioning
confidence: 99%